Study and evaluation of sinus infections with nasal polyps (Eurasian Medical Research Periodical, 2022)
50 patients were collected from Azady Teaching Hospital, Kirkuk, Iraq. This paper focuses on the Study and evaluation of sinus infections with nasal polyps, in addition to its relationship to the cognitive functions of patients. In this study, the severity of symptoms before and after surgery, which included nasal congestion and runny nose, as well as headache and snoring, and the results of preoperative and postoperative cognitive tests were evaluated for the group of patients. The statistical analysis programs SPSS soft 20 in addition to MS EXCEL were used and relied on them in analyzing data and patient outcomes. The study found a significant improvement after surgery. The study also showed through the results that cognitive functions recorded poor results when compared to the results of postoperative patients.